2018
DOI: 10.1002/pds.4405
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sudden sensorineural hearing loss in adults using phosphodiesterase type 5 inhibitors: Population‐based cohort study

Abstract: Use of PDE5 inhibitors is associated with a small but significantly increased risk of sudden SNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…According to the National Institute on Deafness and Other Communication Disorders 100 (https://www.nidcd.nih.gov/health/sudden-deafness), the drug-induced SSHL is characterized by a sudden or rapid loss of hearing and occurs in approximately 4,000 cases per year with an unknown etiology. 101 Liu et al 102 recently reported that the use of PDE-5 inhibitors is associated with a small but significantly increased risk of SSHL. Compared to nonuse, Liu et al 102 reported an adjusted hazard ratio of 1.25 (1.01-1.55) for current use with a risk difference of 1.97 (1.12-2.82) per 10,000 person-years.…”
Section: Predicting Ototoxicity Liability Based On Clinical Renal Patmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the National Institute on Deafness and Other Communication Disorders 100 (https://www.nidcd.nih.gov/health/sudden-deafness), the drug-induced SSHL is characterized by a sudden or rapid loss of hearing and occurs in approximately 4,000 cases per year with an unknown etiology. 101 Liu et al 102 recently reported that the use of PDE-5 inhibitors is associated with a small but significantly increased risk of SSHL. Compared to nonuse, Liu et al 102 reported an adjusted hazard ratio of 1.25 (1.01-1.55) for current use with a risk difference of 1.97 (1.12-2.82) per 10,000 person-years.…”
Section: Predicting Ototoxicity Liability Based On Clinical Renal Patmentioning
confidence: 99%
“…101 Liu et al 102 recently reported that the use of PDE-5 inhibitors is associated with a small but significantly increased risk of SSHL. Compared to nonuse, Liu et al 102 reported an adjusted hazard ratio of 1.25 (1.01-1.55) for current use with a risk difference of 1.97 (1.12-2.82) per 10,000 person-years. For recent use, the adjusted hazard ratio was reported to be 1.60 (1.33-1.94) and risk difference was 3.19 (2.24-4.14).…”
Section: Predicting Ototoxicity Liability Based On Clinical Renal Patmentioning
confidence: 99%